Manejo de sistemas de labranzas en suelos de la cuenca del Río Guayas, retos y perspectiva - Pérez Mayorga, Daniel Josué (2020)
Soil tillage is also known as soil preparation, it aims to create favorable conditions for the development of a specific crop, from seed germination, root and plant growth in general, on certain occasions it is essential for fruit formation. tillage is the set of techniques and operations of the first and second degree that are carried out to prepare a seed bed for the development of a specific crop, whether short, long or perennial. It produces generally unfavorable modifications from the point of view of the conservation of some soil properties: Integral degradation of the soil resource (physical, chemical and biological properties), increased hydric and wind erosion of agricultural surfaces and gradual loss of productivity of the floors. the Guayas basin belongs to the western slope, it constitutes the most important fluvial system of the southwestern Pacific coast, it is made up of seven sub-basins whose drainage network originate in the western foothills of the Andes mountain range and on the eastern slope of the Chongón-Colonche Costanera Mountain Range that make up the Daule and Babahoyo rivers, which join their flows 5 kilometers before the city of Guayaquil giving origin to the Guayas River, which has a length of 93 km from La Puntilla in the Guayas province to Punta Arenas on the Puná Island (estuary) to empty into the Pacific Ocean in the Gulf of Guayaquil. The types of tillage that are managed in the Rios Guayas basin are: conventional tillage, traditional or conventional tillage, minimal or conservation tillage, zero tillage or no-till and precision agriculture. During the analysis of the study carried out by means of digital and physical publications, it was determined that the producers need technical training to help them base and obtain new knowledge on soil management, at the same time not all of them have the same resources to improve their technical implementation, although other farmers are affected by the area and only identify with a tillage system because the place does not allow them to adapt other soil tillage.